Pusa Hara Baingan 1: A new green brinjal for commercial cultivation - Kumar, Ravinder; Munshi, A D; Saha, Partha; Behera, T K; Lyngdoh, Y A; Tomar, B S (Indian Horticulture, 2020)
Brinjal is one of the most common, popular and principle vegetable crop grown worldwide for its excellent food value, shape, size and colour. It is also known as ‘Poor Man’s crop’ as it is mainly grown by the small and marginal farmers. It is highly productive having wide adaptation and easily available throughout the India. Brinjal is also a good source of phytochemicals such as phenolic acid (Chlorogenic acid), flavonoids and anthocyanin which act as antioxidants protecting the body against many degenerative diseases. Pusa Hara Baingan 1 is the first green coloured oval fruited variety which has been released and recommended by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for cultivation in National Capital Region of Delhi including Delhi and its adjoining areas i.e states of Haryana, Rajasthan and Uttar Pradesh.